Strengthening of a Fibre-Matrix Interface: A Novel Method Using Nanoparticles - Sudhir Tiwari; J. Bijwe; S. Panier (Nanomaterials and Nanotechnology)
The surface of carbon fabric (CF) was treated with nanoparticles (NPs) of Ytterbium fluoride (YbF3) (40‐80nm size) in various amounts (0, 0.1, 0.3 and 0.5wt%) to improve its wettability with a Polyetherimide (PEI) matrix. The effect of treatment on the fibres of the CF was also studied by adhesion testing and fibre tow tension testing. An improvement in wettability with PEI and a slight reduction in the tensile strength of the CF was observed in these tests. Fourier transform infrared‐attenuated total reflectance spectroscopy (FTIR‐ATR) indicated the addition of functional groups on the fabric after treatment. Micro‐ Raman spectroscopy (MRS) showed a slight distortion in the structure of the CF due to the treatment. Increased roughness of the fibre surface and adhesion of NPs on the fibre surface were observed by field emission scanning electron microscopy (FESEM). Composites were developed based on untreated and surface‐treated CFs by impregnation techniques. The composites were analysed for interlaminar shear strength (ILSS) and a maximum improvement of 61% was observed for the 0.3% concentration of YbF3, followed by a slight decline in ILSS, indicating that it was the optimum dose.